The nurse’s role in coping with leprosy: potentialities and challenges (Research, Society and Development, 2023)
Introduction: To identify the main findings of nursing care directed to patients who had leprosy, from the mildest spectrum to the severe ones. Methodology: Objetivo: identificar los principales hallazgos de la atención de enfermería dirigidos a pacientes que han tenido lepra. This is a bibliographical, qualitative research that selected and gathered scientific articles from the following platforms: CAPES, SciELO and BVS. As inclusion criteria, studies published in the last 10 years, in Portuguese and English, were listed. Results: Thus, 27 articles were found that after applying the established criteria 12 remained, which after light reading it was reduced to 10 followed by a full reading that resulted in the selection of 5 articles that make up this research, represented in Table 1. In the thematic analysis, two classifications emerged: “Nursing professionals: potentialities and challenges of care for patients with leprosy” and “Epidemiological data: contributions to nursing care in the health of patients with leprosy”. Conclusion: Despite the scarcity of research that addressed the theme, it was possible to identify the contributions of nurses over the last decade and consolidate their importance, both in terms of epidemiological surveillance actions and in leadership and assistance with the nursing team. Reiterating the impact of health education actions on the current and real situation of each locality for which they are responsible.